Development of Al-Mg Alloy for the protection of steel structure in 3.5% Nacl - Mistry Nacl, V. A.; Dani, M. S.; Dave, I. B. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Aluminium (Al) is thoroughly used as a sacrificial metal for the protection of steel in seawater. Aluminium is rarely used as a sacrificial anode without being alloyed due to its built-in properties to get passivates and form a passive layer and the continuity of its layer depends on the chemical composition and microstructure. In this paper, Aluminium-Magnesium(5xxx) system is considered because magnesium remarkably affects the chemical properties by changing the microstructure of Aluminium from a homogeneous solid solution to a complex structure with multiple intermetallic phases. In this research work developing Aluminium-Magnesium alloys containing 2.5 and 4.5 weight percent magnesium. The microstructures of pure aluminium and developed alloys were studied and the effect of the distribution of magnesium whether as a second phase particle, intermetallic compound or precipitates on the performance of aluminium sacrificial anode was discussed. Standard weight loss method and potentiodynamic tests are used to evaluate the performance of alloy sacrificial anode. The result shows that as the magnesium content increases corrosion rate of developed alloy increases and corrosion potential shifts in more negative directions. Corrosion potential is increased by 250 mV at 4.5% magnesium because of the formation of an intermetallic compound of aluminium& Magnesium (β phase - Al3Mg2) at the grain boundary. Magnesium improves the corrosion rate of developed alloy, it acts as a depassivators for the passive film of Aluminium by forming intermetallic compound and this compound has different electrochemicalproperties that leads to corrosion of aluminium and improves the performance of aluminium sacrificial anode.